The Role of Influencers and Product Quality in Purchasing Decisions of Honda BRIO in Surabaya City Mediated by Brand Image - Atthariq Alkausar Herdiyanto; Endi Sarwoko (Fakultas Ekonomika dan Bisnis, Universitas Kanjuruhan Malang, Indonesia, 2026)
This study aims to analyze the influence of influencer and product quality on purchase decisions for Honda Brio cars in Surabaya, as well as to analyze the role of brand image as a mediator. The study utilized a quantitative methodology via a survey of 150 participants aged 20-45 years, who are either current or prospective consumers of Honda Brio, data were analyzed using PLS-SEM. The results indicate that influencers do not have a direct effect on purchase decisions but strongly influence brand image. Conversely, product quality has a direct and indirect effect through brand image. Brand image was found to be a full mediator between influencers and purchase decisions, as well as a partial mediator between product quality and purchase decisions. These findings confirm that for automotive products, purchase decisions are more determined by product quality and brand image than by direct promotion from influencers.